2015
DOI: 10.1063/1.4927289
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation and magnetic properties of rapidly solidified Mn-Al-C alloys modified with Zr

Abstract: Mn 54Àx Al 43 C 3 Zr x (x ¼ 1, 3) alloys were prepared by rapid solidification followed by heat treatment to produce the ferromagnetic s phase. The substitution of Zr for Mn in the structure resulted in an increase of the saturation magnetization (M s ) compared to that of Mn 54 Al 43 C 3 . While the highest M s (128 6 1 emu/g) was obtained in Mn 53 Al 43 C 3 Zr 1 , the coercivity was also improved to 1.62 kOe, compared to 1.25 kOe for Mn 54 Al 43 C 3 . To further improve the coercivity through grain refinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…An M s of ~128 Am 2 /kg was reported in the samples with Zr substitution for Mn and high C content samples with 72 wt. % Mn [ 13 , 25 ]. We also studied the effect of magnetic field during annealing on the phase transformation and found that the magnetic field has little effect on the saturation magnetization of the final product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An M s of ~128 Am 2 /kg was reported in the samples with Zr substitution for Mn and high C content samples with 72 wt. % Mn [ 13 , 25 ]. We also studied the effect of magnetic field during annealing on the phase transformation and found that the magnetic field has little effect on the saturation magnetization of the final product.…”
Section: Resultsmentioning
confidence: 99%
“…The L1 0 structured τ-phase MnAl, usually prepared by annealing the hexagonal ε-phase MnAl at moderate temperatures, is attracting increasing research interests over decades for its low cost and high performance as promising rare earth free magnets [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The metastable nature of τ-MnAl usually results in its decomposition during prolonged annealing or high temperature processing [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies on MnAl‐based alloys were focused on achieving a higher fraction of τ ‐phase and thus a higher saturation magnetization ( M s ), understanding the ε → τ phase transformation mechanism, and enhancing the magnetic performance, particularly the coercivity, via various methods . So far high‐purity τ‐phase has been prepared and there is not much space for improving M s . Currently, the ε → τ phase transformation mechanism is also well‐known and the ε → τ process can be controlled by optimized annealing conditions .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most of the previous studies on MnAl-based alloys were focused on achieving a higher fraction of τ-phase and thus a higher saturation magnetization (M s ), [3] understanding the ε ! τ phase transformation mechanism, [4,5] and enhancing the magnetic performance, particularly the coercivity, via various methods. [3,[6][7][8] So far high-purity τ-phase has been prepared and there is not much space for improving M s .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation